2018
DOI: 10.1080/14397595.2018.1436028
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of TRIM21 in interferon signature of systemic lupus erythematosus

Abstract: Our study showed ubiquitin-dependent proteasomal degradation of IRFs was impaired in anti-TRIM21 antibody-dependent and -independent fashions, leading to amplification of IFN signature in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 57 publications
1
22
0
1
Order By: Relevance
“…Anti-SS-A Ab is observed in sera of patients with autoimmune diseases such as SLE and Sjögren's syndrome, and TRIM21 is one of the autoantigens that bind to anti-SS-A Ab (57,58). We have shown that negative correlation between TRIM21 and type I IFNs expression, which is seen in PBMCs from healthy controls, disappeared in those from SLE patients, especially those with anti-TRIM21 Ab seropositivity (21). In this study, the differentiation from resting B cells to plasmablasts and Ab production were significantly increased in SLE patients with anti-TRIM21 Ab seropositivity as compared to those negative for anti-TRIM21 Ab.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Anti-SS-A Ab is observed in sera of patients with autoimmune diseases such as SLE and Sjögren's syndrome, and TRIM21 is one of the autoantigens that bind to anti-SS-A Ab (57,58). We have shown that negative correlation between TRIM21 and type I IFNs expression, which is seen in PBMCs from healthy controls, disappeared in those from SLE patients, especially those with anti-TRIM21 Ab seropositivity (21). In this study, the differentiation from resting B cells to plasmablasts and Ab production were significantly increased in SLE patients with anti-TRIM21 Ab seropositivity as compared to those negative for anti-TRIM21 Ab.…”
Section: Discussionmentioning
confidence: 77%
“…It is conceivable that the high expression of IFN signature in SLE may be responsible for increased expression of TRIM21 as its suppression mechanism. Furthermore, our previous study showed that a negative correlation is observed between the expression of IFN signature mRNA and TRIM21 mRNA in healthy controls and SLE patients without anti-TRIM21 Ab who are considered to have normal function of TRIM21, but the correlation disappeared in SLE patients with anti-TRIM21 Ab (21). In this context, it was suggested that the function of TRIM21 is impaired by anti-TRIM21 Ab in patients with SLE.…”
Section: Aberrant B-cell Differentiation and Ab Production In Sle Patmentioning
confidence: 95%
See 2 more Smart Citations
“…The uncleaned apoptotic components which recognized by both the innate and the adaptive immune systems can trigger the pathogenesis of SLE. Therefore, the dysregulation of effective genes involved in the clearance of apoptotic components has a fundamental role in SLE [41][42][43][44][45]. Remarkably, we showed upregulation of MACROH2A1, SNRPD3, and Ro60 and downregulation of MACROH2A2, TRIM21…”
Section: Discussionmentioning
confidence: 62%